High mortality and violence among refugees and returnees from West Darfur, Sudan arriving in Chad, 2023: results from three retrospective mortality surveys - Emmanuel Grellety; Erica Simons; Pascal Ouedraogo; Christophe Garnier; Claire Nicolet; Jessica Sayyad-Hilario; Emilie Villet; Adam Ahmat Mahamoud; Jérôme Tubiana (BMJ Global Health)
Introduction Fighting erupted on 15 April 2023 in Sudan between the army and the paramilitary Rapid Support Forces. By September 2023, more than 420 000 people had fled to Chad. To assess the impact of the conflict on the displaced populations, several surveys were conducted. We aimed to describe retrospective crude and under-5 mortality rates, reported causes of death and the frequency and type of violent events experienced by populations displaced to camps in eastern Chad.Methods Cross-sectional surveys were carried out in August and September 2023 among displaced populations in Toumtouma, Ourang and Arkoum camps. Each survey included retrospective mortality and frequency and type of violent events experienced. All surveys considered precrisis and crisis phases.Results In all sites, the crude mortality rate (CMR) was significantly higher in the crisis phase than in the precrisis phase. The CMR was particularly elevated among populations in Ourang camp (CMR: 2.25 deaths/10 000 persons/day (95% CI 1.77 to 2.74) in crisis phase versus CMR: 0.11 deaths/10 000 persons/day (95% CI 0.02 to 0.20) in precrisis phase). Violence was the leading reported cause of death in all sites. Among households in Ourang, more than 90% came from El Geneina (Sudan) and more than one in 10 of all men aged 30 and over died of violent causes. In Toumtouma, Ourang and Arkoum camps, the overall frequency of violence among households was 3.3%, 11.7% and 4.4%, respectively, with beatings and shooting most frequently cited.Conclusions In the three camps investigated, excess mortality was observed among households during the crisis phase attributed largely to deaths caused by violence among men. The population in Ourang camp, largely from El Geneina, were particularly affected by the violence, with the CMR 20 times higher than in the precrisis period and mortality rates exceeding the standard emergency threshold (1 death/10 000 persons/day).